2003
DOI: 10.1287/orsc.14.1.32.12815
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Trustworthiness Within the Organization: The Moderating Impact of Communication Frequency on Trustor and Trustee Effects

Abstract: This paper investigates the antecedents of intraorganizational trust and, more specifically, how the frequency of communication between trustor and trustee moderates the impact of these factors on perceived trustworthiness. Data on 157 dyadic relationships among 50 senior managers within a multinational corporation confirm that the effect of both trustor, as well as trustee characteristics on the level of perceived trustworthiness, is moderated by the frequency of communication between the two parties. As comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
143
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(155 citation statements)
references
References 37 publications
7
143
0
5
Order By: Relevance
“…To control for the direction of the relationship, we coded whether a knowledge source was the respondent's direct supervisor (1) or a subordinate (0). Finally, as previous research has shown that communication frequency affects trust (Becerra & Gupta, 2003;Chattopadhyay, 1999;McAllister, 1995), we combined two items as a control. The first, adapted from Hansen (1999), asked how often the respondent had communicated with the source prior to seeking him or her out as a knowledge source on the project in question, from daily (1) to once every three months or less (or never) (7) (M ϭ 5.53, SD ϭ 2.26).…”
Section: Methodsmentioning
confidence: 99%
“…To control for the direction of the relationship, we coded whether a knowledge source was the respondent's direct supervisor (1) or a subordinate (0). Finally, as previous research has shown that communication frequency affects trust (Becerra & Gupta, 2003;Chattopadhyay, 1999;McAllister, 1995), we combined two items as a control. The first, adapted from Hansen (1999), asked how often the respondent had communicated with the source prior to seeking him or her out as a knowledge source on the project in question, from daily (1) to once every three months or less (or never) (7) (M ϭ 5.53, SD ϭ 2.26).…”
Section: Methodsmentioning
confidence: 99%
“…As organizational representatives people use their natural propensity to trust, professional competences and organizational procedures to shape the context for trust in future relations. Development of inter-organizational relations is closely connected to strengthening interpersonal relations by organizational processes of boundary spanning, open and partner-oriented communication, mutual learning and engagement which in turn affects pro co-operational behavior [Hakansson et al 2009;Ford et al 2011;Blomqvist and Seppänen 2003;Creed and Miles 1996;Becerra and Gupta 2003;Dirks and Ferrin 2002;Kramer 1999;Malhotra and Murnighan 2002]. Interpersonal trust as a part of organizational social capital may affect the efficiency of IORs through employees' organizational commitment and identification processes [Bakiev 2013].…”
Section: Interpersonal Trustmentioning
confidence: 99%
“…The operationalization of trust draws on the work of Fink and Harms (2012), Fink and Kessler (2010) and Adler (2001) and comprises several dimensions: As trust is reflected in the willingness to forgo individual short-term profits for the sake of joint long-term profits, selfcommitted cooperators have no short-term perspective (Becerra and Gupta 2003;Gulati 1995). Thus, trust also shows up in a firm's willingness to take the risk that its expectations concerning its cooperation partners' future behavior might not be met (Malhotra and Murninghan 2002).…”
Section: Explanatory Variablesmentioning
confidence: 99%